Iron deficiency and iron deficiency anaemia in women. (April 2017) - Percy, Laura; Mansour, Diana; Fraser, Ian
Abstract : Iron deficiency (ID) is the most common micronutrient deficiency worldwide with >20% of women experiencing it during their reproductive lives. Hepcidin, a peptide hormone mostly produced by the liver, controls the absorption and regulation of iron. Understanding iron metabolism is pivotal in the successful management of ID and iron deficiency anaemia (IDA) using oral preparations, parenteral iron or blood transfusion. Oral preparations vary in their iron content and can result in gastrointestinal side effects. Parenteral iron is indicated when there are compliance/tolerance issues with oral iron, comorbidities which may affect absorption or ongoing iron losses that exceed absorptive capacity. It may also be the preferred option when rapid iron repletion is required to prevent physiological decompensation or given preoperatively for non-deferrable surgery. As gynaecologists, we focus on managing women's heavy menstrual bleeding (HMB) and assume that primary care clinicians are treating the associated ID/IDA. We now need to take the lead in diagnosing, managing and initiating treatment for ID/IDA and treating HMB simultaneously. This dual management will significantly improve their quality of life. In this chapter we will summarise the importance of iron in cellular functioning, describe how to diagnose ID/IDA and help clinicians choose between the available treatment options. Highlights: Iron deficiency (ID) is the most common micronutrient deficiency worldwide with >20% of women experiencing it during their reproductive lives. Oral preparations vary in their iron content and can result in gastrointestinal side effects. Parenteral iron is indicated when there are compliance/tolerance issues with oral iron, comorbidities, which may affect absorption or ongoing iron losses that exceed absorptive capacity. As gynaecologists, we focus on managing women's heavy menstrual bleeding (HMB) and assume that primary care clinicians are treating the associated ID/IDA. We now need to take the lead in diagnosing, managing and initiating treatment for ID/IDA and treating HMB simultaneously. In this study, we will summarise the importance of iron in cellular functioning, describe how to diagnose ID/IDA and help clinicians choose between the available treatment options.